Texturized vegetable protein from a faba bean protein concentrate and an oat fraction: Impact on physicochemical, nutritional, textural and sensory properties - Cátia Saldanha do Carmo; Anne Rieder; Paula Varela; Hanne Zobel; Tzvetelin Dessev; Solveig Nersten; Sara M. Gaber; Stefan Sahlstrøm; Svein Halvor Knutsen (Future Foods, 2023)
Texturized vegetable protein (TVP) from a blend of faba bean protein concentrate and an oat beta-glucan rich fraction was produced by low-moisture extrusion to combine nutritional benefits of both ingredients. The effect of extrusion conditions (temperature in zone 6 (HZ6), feed rate (FR) and moisture content (MC)) on physicochemical, nutritional, textural, and sensory attributes was studied. Overall, effect of the FR and MC of the blend showed greater impact on TVP properties rather than the temperature. TVPs produced at 28.5%, 5 Kg/h and 150⁰C and at 30.8%, 4 Kg/h and 160⁰C for MC, FR and HZ6, respectively, presented improved properties to be further formulated into a meat analogue product. The beta-glucan content of TVP (5.6g/100g dm) was high enough to reach >1 g beta-glucan per serving in a final food product (e.g., vegan burger), which qualifies for the health claim “reduces low-density lipoprotein (LDL)-cholesterol” approved by the European Food Safety Authority. The combination of these ingredients resulted simultaneously in an improved composition of essential amino acids and increased the protein quality of the blend as the calculated digestible indispensable amino acid score (DIAAS) improved from 72.2 (beta-glucan rich fraction alone) or 76.1 (faba bean protein concentrate alone) to 90.2 (blend).